ANALISIS ORGANIZATIONAL CITIZENSHIP BEHAVIOR ( OCB ) DAN MOTIVASI TERHADAP KINERJA KARYAWAN KANTOR POS DI KOTA BATAM - Wasiman; Mauli Siagian (Postgraduate Management Journal, 2023)
This study aims to determine the effect of Organizational Citizenship Behavior (OCB) and motivation on employee performance at post office service companies in Batam City. This study used primary data through questionnaires which were distributed to post office service company employees in Batam City. Questionnaires were distributed to a total of 120 respondents. Based on the results of the questionnaire distribution, it is known that the results of the validity test show that all indicators in the OCB variable statement and all indicators in the motivational variable statement show valid results, this means that the validity test level of all data is valid and can be continued to the reliability test stage. The reliability test means that the OCB variable, motivational variable and employee performance variable also show reliable results. The results of the normality test show that all data processing results show normal results. The results of the test and t test and the results of the f test can be said that OCB and motivation have a significant effect on the performance of post office delivery service company employees in Batam City. The result of the coefficient of determination (R2) is 0.810, meaning that employee performance variables can be explained by OCB and motivation variables by 81% while 19% are other variables outside the study.